Synergistic activity of Limosilactobacillus reuteri KUB-AC5 and water-based plants against Salmonella challenge in a human in vitro gut model - Mok, Kevin; Honwichit, Orranich; Funnuam, Thanyakan; Charoensiddhi, Suvimol; Nitisinprasert, Sunee; Nielsen, Dennis Sandris; Nakphaichit, Massalin (Scientific reports, 2024)
A synbiotic is a combination of live microorganisms and specific substrates that are selectively utilized by host microorganisms, resulting in health benefits for the host. Previous studies have demonstrated the protective effects of L. reuteri KUB-AC5 against Salmonella infection in chicken and mouse models. The probiotic activity of L. reuteri KUB-AC5 in these hosts was influenced by nutritional supplements. Water-based plants contain significant amounts of carbohydrates, particularly dietary fiber and proteins, making them potential prebiotic substrates. In this study, four water-based plants ( Ulva rigida , Caulerpa lentillifera , Wolffia globosa , and Gracillaria fisheri ) were screened for their ability to support the growth of L. reuteri KUB-AC5. Under monoculture testing, U. rigida exhibited the highest capacity to support the growth of L. reuteri KUB-AC5 and the production of organic acids, including acetic acid, lactic acid, and propionic acid ( p ≤ 0.05). In co-culture experiments, the synbiotic combination of U. rigida and L. reuteri KUB-AC5 demonstrated the potential to eliminate Salmonella Typhimurium DMST 48437 when inoculated at 10 4 CFU/mL within 9 h. The synbiotic activities of U. rigida and L. reuteri KUB-AC5 were further investigated using an in vitro human gut model. Compared to the probiotic treatment, the synbiotic combination of L. reuteri KUB-AC5 and U. rigida showed significantly higher levels of L. reuteri KUB-AC5 (5.1 log copies/mL) and a reduction of S . Typhimurium by 0.8 log (CFU/ml) after 24 h ( p ≤ 0.05). Synbiotic treatment also significantly promoted the production of short-chain fatty acids (SCFAs), including butyric acid, propionic acid, and acetic acid, compared to prebiotic and probiotic treatments alone ( p ≤ 0.05). Furthermore, the synbiotic formulation modulated the in vitro simulated gut microbiome, enhancing putatively beneficial gut microbes, including lactobacilli, Faecalibacterium , and Blautia . Our findings demonstrated that L . reuteri KUB-AC5, in combination with U . rigida , exhibited synergistic activity, as indicated by increased viability, higher anti-pathogenicity toward Salmonella , and the ability to modulate the gut microbiome.